A Struggle Between Loyalty and Commodification : Scandinavian Football Fans - Radmann, Aage; Andersson, Torbjörn; Herd, Katarzyna (Palgrave Macmillan, 2023)
This chapter will give insight into the Nordic football fandom culture describing supporter culture in all five Nordic countries, Sweden, Denmark, Norway, Iceland, and Finland. Focusing on history, identities, policies, and politics the authors discuss if a specific “Nordic supporter culture” exists and if there are significant perspectives in this culture compared to other football fandom cultures. Sweden has the most devoted fans when it comes to club football in the Nordic countries and Denmark and Iceland when we talk about fans supporting the national teams. Scandinavia of today has a strong supporter culture and good attendances at football matches. While following the development patterns seen in many European countries, football fans in Scandinavia have developed region-specific modes of creative engagement with the game. Supporters not only encourage their clubs, they also provide a modern commentary and criticism of social and economic changes within the globalized football world. The evolution of football fans, exemplified by the Scandinavian context and taking neighboring countries into consideration, is paired with socio-temporal national realities and European developments. Thus, the activities on Scandinavian football arenas result in producing identities and histories relevant in the Nordic context.